Effectiveness of Bengkung Post Natal Care on Size of Diastasis Rectus Abdominis (DRA) - Arfiana Arfiana (Universitas Negeri Semarang, 2023)
Diastasis Rectus Abdominis can cause various problems in the puerperal mother, including causing weakness of the abdominal wall, thus endangering for future pregnancies, can cause the occurrence of a hanging stomach, so that it inhibits the process of the baby's head entering the birth canal, disrupting maternal activity, resulting in back pain, pelvic floor dysfunction, hernias, and cosmetic disorders that affect the psychological childbirth. Pelvic pain is the most common manifestation of Diastasis Rectus Abdominis (DRA). This study aims to determine the effectiveness of the curve to reduce DRA. The study was conducted in the working area of ​​​​the North Magelang Public Health Center in Magelang City, with 30 postpartum mothers and put on postnatal care curves, for 10 days, which were divided into intervention groups (use of curves since in the first 7 days of puerperium / early) and control groups (use of curves started after 7 days postpartum / later). Wilcoxon test results show that the use of curves both early and slow is effective to reduce the size of the DRA and the Mann Whitney test shows that there is no significant decrease in the size of the DRA in the use of curvature in the early or slow postpartum period, but the mean and standard deviation indicate that early use can reduce the size of the DRA more. Health workers are expected to adopt the use of curves to help accelerate the reduction in the size of postpartum maternal DRA.